Impact of Fermentation Conditions on the Extraction of Phenolics and Sensory Characteristics of Mangosteen Wine - Shrestha, Tenzing Dasel; Kunathigan, Viyada; Kitsawad, Kamolnate; Panprivech, Siriwan (Applied Science and Engineering Progress, 2021)
Phenolics play a major role in determining the quality of wine. This study focuses on the impact of fermentation conditions (varying pericarp content: 0, 5, 7.5, and 10% (w/v); Saccharomyces cerevisiae strain: Montrachet- UCD #522 and Pasteur Red-UCD #904) on the extraction of phenolics and sensory characteristics of mangosteen wine at 30 ± 2°C. The addition of pericarp showed a significant effect on color intensity, but the choice of strain of yeast used has no effect. With increasing percentage of pericarp added, the amount of phenolics, tannins, and anthocyanins increased, with the highest total phenolic content to be 4,000 mg/L catechin equivalent at the end of fermentation. At lower percentage of added pericarp, the yeast induced no apparent difference to the sensory characteristics, but at higher percentage the difference was more apparent. Wine with lower percentage of pericarp added had higher intensity of mangosteen pulp flavor, whereas wine with higher percentage of pericarp has more mangosteen pericarp characteristics. Pasteur Red contributed to a higher degree of fruity and floral aroma/flavor, while Montrachet contributed to a more intense body.